hikaayaat kaliila wa-dimna li-tulaab al-lughat al-carabiyya (Tales from Kalila wa Dimna for Students of Arabic [retold]): By Munther A Younes (Ithaca, NY: Spoken Language Services, 2001. 206 pages, 3 audio CDs.) (American Journal of Islam and Society, 2003)
The title Kalila wa Dimna first came to my attention long ago in my secondyear of Arabic language study. Ahmad Amin mentions Kalila waDimna in passing in his autobiography, Hayati (Cairo: 1952), an excerpt ofwhich I read in Farhat Ziadeh’s Reader in Modern Literary Arabic. Overthe years, I tried occasionally to read a bit of the original and found the classicalArabic intimidating. The task of reviewing Munther Younes’s retellingof these stories represented the opportunity to taste the stories’ flavor withoutthe drudgery of dictionary look-up. Among other accomplishments,Younes simplifies the grammar and lexicon to the point where intermediatestudents of Arabic will understand what they read without excessive struggle.This review will touch upon the structure and substance of Kalila waDimna itself and Younes’ approach to retelling the stories and their utilizationas an Arabic language teaching tool.In the West, most of us hear and then read Aesop’s Fables as children.These stories, which date back as far as 620 BCE, feature anthropomorphicanimals who play out their dramas and conflicts in order to teach a moral.Kalila wa Dimna, attributed to the Indian author Bidpai and written inSanskrit during the third century, does much the same, but also includes asmattering of human characters. As Younes tells us, the Sassanid KingKhosro Anoushrawan sent his physician Burzuwayh to India to collect andtranslate Bidpai’s fables into Persian. In the process, Burzuwayh added storiesby other authors. What had now become a book was then translatedinto Syriac in 570; 200 years later, Abdullah ibn al-Muqafac translated itinto Arabic. Since its Arabization some 12 centuries ago, Kalila wa Dimna